Cross disciplinary approaches in collaborative research for a sustainable society. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2009)
Scientific advancement and modern development are obviously closely linked. Most progress has come from scientific research that resulted from basic research approaches, usually within single disciplines. The traditional role of research was thus to contribute to the advancement of development by generating knowledge with technological applications such as new information technologies, biotechnology and transport and energy-transforming technologies.